Parity improves anti-tumor immunity in breast cancer patients - Krause, Anna-Lena; Schütz, Florian; Boudewijns, Mark; Wallwiener, Markus; Golatta, Michael; Rom, Joachim; Heil, Jörg; Sohn, Christof; Schneeweiss, Andreas; Domschke, Christoph (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.20756 Anna-Lena Krause, Florian Schuetz, Marc Boudewijns, Maria Pritsch, Markus Wallwiener, Michael Golatta, Joachim Rom, Joerg Heil, Christof Sohn, Andreas...